A Human‐Based Functional NMJ System for Personalized ALS Modeling and Drug Testing. Issue 11 (11th August 2020) - Guo, Xiufang; Smith, Virginia; Jackson, Max; Tran, My; Thomas, Michael; Patel, Aakash; Lorusso, Eric; Nimbalkar, Siddharth; Cai, Yunqing; McAleer, Christopher W.; Wang, Ying; Long, Christopher J.; et al.
Abstract: Loss of the neuromuscular junction (NMJ) is an early and critical hallmark in all forms of amyotrophic lateral sclerosis (ALS). Herein, a functional NMJ disease model is developed by integrating motoneurons (MNs) differentiated from multiple ALS‐patients' induced pluripotent stem cells (iPSCs) and primary human muscle into a chambered system. NMJ functionality is tested by recording myotube contractions while stimulating MNs by field electrodes and a set of clinically relevant parameters is defined to characterize the NMJ function. Three ALS lines are analyzed, two with SOD1 mutations and one with an FUS mutation. The ALS‐MNs reproduce pathological phenotypes, including increased axonal varicosities, reduced axonal branching and elongation, and increased excitability. These MNs form functional NMJs with wild type muscle, but with significant deficits in NMJ quantity, fidelity, and fatigue index. Furthermore, treatment with the Deanna protocol is found to correct the NMJ deficits in all the ALS mutant lines tested. Quantitative analysis also reveals the variations inherent in each mutant line. This functional NMJ system provides a platform for the study of both fALS and sALS and has the capability of being adapted into subtype‐specific or patient‐specific models for ALS etiological investigation and patient stratification for drug testing. Abstract : This study develops a functional neuromuscular junction (NMJ) model for amyotrophic lateral sclerosis (ALS) by integrating motoneurons differentiated from ALS‐patients' induced pluripotent stem cells (iPSCs) and establishes a set of clinically relevant parameters to analyze ALS pathology and treatment with the Deanna protocol. This platform can be applied for developing patient‐specific models for both fALS and sALS.